Dampak Pembiayaan Terhadap Jaringan Sosial Dan Kesejahteraan Anggota BMT - Andresna Ristianto; Dina Yustisi Yurista (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2021)
This study aims to determine the relationship between BMT Hubbul Wathon with members and member welfare through financing conducted. This type of research is descriptive qualitative, the data used are primary data, with data collection methods through observation, interviews, and literature studies. The population in the study was the Hubbul Wathon BMT with a sample of 11 people.Based on the results of the analysis shows that financing contributes to helping members who are in need of capital to develop the business that members run. So that it impacts on members by increasing the income of members, achieving high education and meeting economic needs. So that the financing can affect the welfare of members. And the establishment of a good relationship between members and the BMT Hubbul Wathon through financing conducted so that there is trust between the two parties.